Towards the Development, Maintenance and Standardized Phenotypic Characterization of Single-Seed-Descent Genetic Resources for Chickpea - Rocchetti, Lorenzo; Gioia, Tania; Logozzo, Giuseppina; Brezeanu, Creola; Pereira, Luis Guasch; De la Rosa, Lucía; Marzario, Stefania; Pieri, Alice; Fernie, Alisdair; Alseekh, Saleh; Susek, Karolina; Cook, Douglas; et al. (Wiley Periodicals, 2022)
Here we present the approach used to develop the INCREASE “Intelligent Chickpea” Collections, from analysis of the information on the life history and population structure of chickpea germplasm, the availability of genomic and genetic resources, the identification of key phenotypic traits and methodologies to characterize chickpea. We present two phenotypic protocols within H2O20 Project INCREASE to characterize, develop, and maintain chickpea single-seed-descent (SSD) line collections. Such protocols and related genetic resource data from the project will be available for the legume community to apply the standardized approaches to develop Chickpea Intelligent Collections further or for multiplication/seed-increase purposes. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC.